KAJIAN LEARNING CONTENT MANAGEMENT SYSTEMS (LCMS) DALAM KERANGKA DISAIN PEMBELAJARAN - Prawiradilaga, Dewi Salma (Jurnal TEKNODIK, 2009)
The article is about a descriptive finding on the function of an LCMS used by the official website of the Department of Curriculum and Educational Technology, Faculty of Education, State University of Jakarta, www.courses.web-bali.net. Based on the observation, there are some principles that may be applied in uploading course content. They are topic analysis and message design principles which should intensively be applied during developing and structuring learning objects in a learning path. Chunk is the main concept in content development. Regarding copyright issue, all parties should respect to those who write or produce creative works accessible through online.